Entre livros e fraldas: uma análise discursiva das representações e práticas institucionais sobre mães estudantes universitárias na UFSCar - Rodrigues, Vanessa Aparecida (Universidade Federal de São Carlos, 2025)
The impact of motherhood on women’s lives has generated debates in many spaces, specially in Brazilian public universities. In this context, the Parent in Science Movement seeks to understand, give visibility to, and propose solutions for the challenges faced by people with children, in the academic and scientific fields in Brazil. Although the current legal framework of access and permanency in higher education represents progress, it still shows a need of specific and comprehensive mechanisms to assist the students diverses demands who balance motherhood and academic life. Inspired by these discussions, this research formulates the following questions: how do institutional documents that regulate higher education discursively construct the image of women in the role of mothers as higher education students? In what way does the construction of these documents, regarding the figure of the “student mother”, influence and condition the discursive practices of mother-students in undergraduate and graduate courses in UFSCar? To answer these questions, we adopted as a theoretical and methodological basis the French Discourse Analysis (DA), based on the propositions of Michel Pêcheux (1969) about discursive formations, discursive memory, interdiscourse and mainly, imaginary formations. Initially, the investigation analyzes the construction historicity of the female roles in Brazilian society, aiming to identify the interdiscursive knowledge that functions as a reservoir of already produced and forgotten discourses that, however, conditionate and make possible the production of new (old) discourses about women. Based on this historical contextualization of women in society and in education, the analysis is directed to a set of eleven institutional documents from the State, which regulate higher education (laws, decrees, ordinances, regulations, regiments and internal policies), seeking to verify the current discursive practices related to women and student motherhood. Subsequently, based on statements taken from posters of student manifestations (expressing the demands of student mothers), we mobilized the concept of interdiscourse to describe/interpret the transversal and pre-constructed discourses that permeate the discourses of these posters. In this way, we demonstrate how discourses from the past, albeit in implicit form, resonate in present discourses, enabling others discursive formations.
Between books and diapers: a discursive analysis of representations and institutional practices about university student mothers in UFSCar
Keywords: Análise do discurso; Formações imaginárias; Maternidade e universidade; Discourse analysis; Imaginary formations; Motherhood and university; LINGUISTICA, LETRAS E ARTES